A PERFECT EXAMPLE OF ALISHER NAVOI’S POETRY - Maksud Asadov (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the poetic features of the great thinker Alisher Navoi’s book, in particular, the content of the poetic text of the art used in the book, the position of the great poet in revealing the worldview and characteristic aspects of his artistic skills.